Información de los medios de comunicación digital La Hora y La Voz populi durante la pandemia, Babahoyo período abril - mayo 2020 - Franco Mosquera, Hipatia Elizabeth (2020)
The Covid-19 pandemic is a disease that has forced changes not only in health care but has also generated technological changes, forcing a new restructuring of the traditional media to carry out news coverage. took into consideration the digital newspapers La Hora and La Voz Populi, to know the type of narrative used to inform the public about the news that occurred during the state of emergency due to the pandemic during the months of April and May 2020. The type of methodology for the analysis of the information presented by the aforementioned media is an observation sheet, which has as its principle the understanding of the type of writing to be used, the hypermedia narrative tools used and the content of The texts. It is concluded that the communication media La Hora and La Voz Populi use an eloquent and laudable narrative, thus proving the reason for their high acceptance among citizens due to the number of subscribers, it is recommended to improve the hypermedia narrative that these digital spaces of the web 2.0 in order to generate a better experience for users, allowing a sequence of events not only in the publication of videos but also in hyper-connection links.